Comparison of prone positioning and extracorporeal membrane oxygenation in acute respiratory distress syndrome: A multicenter cohort study and propensity-matched analysis - Ko-Wei Chang (Journal of the Formosan Medical Association, 2022)
Background/Purpose: Both prone positioning and extracorporeal membrane oxygenation (ECMO) are used as rescue therapies for severe hypoxemia in patients with acute respiratory distress syndrome (ARDS). This study compared outcomes between patients with severe influenza pneumonia-related ARDS who received prone positioning and those who received ECMO. Methods: This retrospective cohort study included eight tertiary referral centers in Taiwan. All patients who were diagnosed as having influenza pneumonia-related severe ARDS were enrolled between January and March 2016. We collected their demographic data and prone positioning and ECMO outcomes from medical records. Results: In total, 263 patients diagnosed as having ARDS were included, and 65 and 53 of them received prone positioning and ECMO, respectively. The baseline PaO2/FiO2 ratio, Acute Physiology and Chronic Health Evaluation II score and Sequential Organ Failure Assessment score did not significantly differ between the two groups. The 60-day mortality rate was significantly higher in the ECMO group than in the prone positioning group (60% vs. 28%, p = 0.001). A significantly higher mortality rate was still observed in the ECMO group after propensity score matching (59% vs. 36%, p = 0.033). In the multivariate Cox regression analysis, usage of prone positioning or ECMO was the single independent predictor for 60-day mortality (hazard ratio: 2.177, p = 0.034). Conclusion: While the patients receiving prone positioning had better outcome, the causality between prone positioning and the prognosis is unknown. However, the current data suggested that patients with influenza-related ARDS may receive prone positioning before ECMO support.